2008
DOI: 10.1186/1746-1448-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the adaptation responses to osmotic and temperature stress in Chromohalobacter salexigens, a bacterium with broad salinity tolerance

Abstract: Chromohalobacter salexigens, a Gammaproteobacterium belonging to the family Halomonadaceae, shows a broad salinity range for growth. Osmoprotection is achieved by the accumulation of compatible solutes either by transport (betaine, choline) or synthesis (mainly ectoine and hydroxyectoine). Ectoines can play additional roles as nutrients and, in the case of hydroxyectoine, in thermotolerance. A supplementary solute, trehalose, not present in cells grown at 37°C, is accumulated at higher temperatures, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
103
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 38 publications
3
103
0
Order By: Relevance
“…Colocalization of the ectoine/hydroxyectoine biosynthetic genes and of ask_ect is not uncommon in microorganisms (39,45,57,62). We extend previous analysis by inspecting the presently available bacterial (1,426) and archaeal (80) genome sequences for ask_ect genes associated with ectoine/hydroxyectoine biosynthetic gene clusters.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Colocalization of the ectoine/hydroxyectoine biosynthetic genes and of ask_ect is not uncommon in microorganisms (39,45,57,62). We extend previous analysis by inspecting the presently available bacterial (1,426) and archaeal (80) genome sequences for ask_ect genes associated with ectoine/hydroxyectoine biosynthetic gene clusters.…”
mentioning
confidence: 91%
“…This finding hints that this particular ask gene (ask_ect) encodes an aspartokinase that could play a specialized role in the biosynthesis of the compatible solute ectoine under osmotic stress conditions. Subsequently, it was observed that a considerable number of ectoine/hydroxyectoine biosynthetic gene clusters are actually followed by an ask gene (39,45,57,62). A comprehensive cohesion group analysis reported by Lo et al (39) showed that the encoded proteins form a distinct subcluster (cohesion group 02 [CG-02]) within the Ask superfamily.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the putative regulatory protein is disrupted by two stop codons and no start codon could be found. In C. salexigens, the orf (gene ectR) was found upstream of ectD (Vargas et al, 2008;Garcia-Estepa et al, 2006). Deletion of the ectR gene resulted in decreasing of hydroxyectoine level at high salinity and high temperature, in comparison to the wild type cells.…”
Section: Ectoine Synthase (Ectc Ec 421108)mentioning
confidence: 99%
“…C. salexigens, a gram-negative aerobic bacterium, is moderately halophilic in nature. It grows at NaCl concentrations ranging between 0.5M and 4M, with an optimum growth at 2.0-2.5M and at an optimum temperature of 37°C [6,7]. Rhizobium etli (R. etli) is gram-negative soil bacteria, which fixes nitrogen and forms an endosymbiosis nitrogen fixing association with roots of legumes.…”
Section: Introductionmentioning
confidence: 99%